Membangun Jiwa Entrepreneur Diwaktu Muda Di Pondok Pesantren Terpadu Al-Mujahidin - Iwan Sulistia; Eka Riyanti Yusuf; Nita Rislawati; Rolly Rezki Ananda; Fevica Dwi Anggreini; Fenty Fauziah; Fitriansyah Fitriansyah; Muhammad Harry Rahmadi (Jurnal Pengabdian Masyarakat Nusantara, 2023)
The importance of the role of learners in the future, therefore entrepreneurship education must be continued and prepared. Entrepreneurship at the basic education level is designed to develop independent, creative, leadership and hardworking traits. To improve and prepare it, socialization or counseling was carried out at the Al-mujahideen Integrated Islamic Boarding School Foundation, Jl Soekarno-Hatta Km 10, Karang Joang Village, North Balikpapan District, Balikpapan City, East Kalimantan. The socialization was held on October 16, 2022, consisting of 82 students. The purpose of this socialization is to provide information about entrepreneurship and build an entrepreneurial spirit. The method of this activity is to provide education, discussion and question and answer, and wilcoxon test is also used to find out the comparison before and after the delivery of the material. The results of this activity are expected that students can gain knowledge about entrepreneurship and develop a desire to become entrepreneurs for the future, the results of the Wilcoxon test state that there are significant differences before and after the delivery of the material. So all students have understood more deeply about entrepreneurial knowledge, developed and built a mindset about entrepreneurship.